Restructuring BOD : COD Ratio of Dairy Milk Industrial Wastewaters in BOD Analysis by Formulating a Specific Microbial Seed - Purnima Dhall; T. O. Siddiqi; Altaf Ahmad; Rita Kumar; Anil Kumar (The Scientific World Journal)
BOD (Biochemical oxygen demand) is the pollution index of any water sample. One of the main factors influencing the estimation of BOD is the nature of microorganisms used as seeding material. In order to meet the variation in wastewater characteristics, one has to be specific in choosing the biological component that is the seeding material. The present study deals with the estimation of BOD of dairy wastewater using a specific microbial consortium and compares of the results with seeding material (BODSEED). Bacterial strains were isolated from 5 different sources and were screened by the conventional BOD method. The selected microbial seed comprises of Enterobacter sp., Pseudomonas sp. BOD : COD (Chemical oxygen demand) ratio using the formulated seed comes in the range of 0.7-0.8 whereas that using BODSEED comes in the ratio of 0.5-0.6. The ultimate BOD (UBOD) was also performed by exceeding the 3-day dilution BOD test. After 90 days, it has been observed that the ratio of BOD : COD increased in case of selected consortium 7 up to 0.91 in comparison to 0.74 by BODSEED. The results were analyzed statistically by t-test and it was observed that selected consortium was more significant than the BODSEED.